Fintech Analysis of E-Mas Development at Bank Syariah Indonesia KCP Adam Malik Medan - Qamara, Lisa; Fauzi Arif Lubis; Aslami, Nuri (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyze the impact of Fintech on the development of E-Mas products at Bank Syariah Indonesia (BSI) KCP Adam Malik Medan. E-Mas products, as an innovation in Islamic banking, must fulfill sharia principles such as clear ownership and legal contracts. This research uses a qualitative approach with Field Research method to explore in depth the influence of Fintech on the development of e-mas services at Bank Syariah Indonesia (BSI) KCP Adam Malik Medan. Data was collected through interviews. The results showed that Fintech plays a positive role in accelerating the digitalization of Islamic banking and increasing gold investment literacy in the community, especially among parents. Nonetheless, Gen Z customers show greater interest in the use of e-mas and other digital features. The success of these services depends not only on technological sophistication, but also on the effectiveness of education, digital infrastructure readiness, and sharia integrity. Therefore, collaboration between banks, regulators, and the community is essential to develop a fair, inclusive, and sustainable Islamic Fintech ecosystem.